Learning Design Using Discord and Jigsaw Strategies to Improve Listening Skills - Ramadhan, Iqbal; Degeng, Made Duanda Kartika; Praherdhiono, Hendry; Bahri, Saiful (SJME (Supremum Journal of Mathematics Education), 2024)
Discusses the challenges faced by the education system in Indonesia as it adapts to the changes brought about by the development of technology and communication. The emergence of Industry 5.0 poses a significant challenge, forcing educational institutions to implement remote learning processes. Terms such as blended learning, hybrid learning, flip-classroom, and others have become ways to integrate online and offline teaching and learning activities. This integration presents new challenges in terms of effectiveness, efficiency, and engagement in designing learning that combines various media and strategies. According to Prof. Punaji (2020) in his book on learning design, learning design is a process that involves planning the needs and objectives of learning, developing teaching media, and systematically implementing an effective and efficient learning system to achieve predetermined learning goals. Various factors, such as materials and activities, student characteristics, curriculum, experimentation, teaching methods and media, and learning evaluation, need to be considered in the development of learning design. Combining learning design with technology is expected to make learning more effective and efficient, leading to optimal results.